FERTILIZANTES PARA CULTIVO ORGÂNICO DE ALFACE (Lactuca sativa L) - RODRIGUES, Pedro Henrique Dias Rodrigues; HAYD, Norton Hayd Rego; ESPINDOLA, Gabriella Alemida dos Santos Espindola; DIONÍZIO, Jéssica Dionizio Vieira; STRANG, Rafael de Sá Strang; BARROS, Luís Gustavo Silva Barros Filho (ANAIS DO ENIC, 2024)
-